Changes in immigrant individualsʼ language attitudes through contact with Catalan: the mirror effect. Issue 4 (1st October 2016) - Cortès-Colomé, Montserrat; Barrieras, Mònica; Comellas, Pere
ABSTRACT: This paper presents the results of a study based on the change in language attitudes experienced by some allochthonous individuals through contact with the sociolinguistic situation in Catalonia. Previous studies have suggested that in some cases, contact with Catalan – a minority language with a valued identity – acts as a stimulus for some foreigners to re-evaluate their own linguistic heritage. The present ethnographic research aims at providing some clues as to how the discovery of a minority language triggers changes in representations and attitudes. The study employed a qualitative methodology based on in-depth open interviews. The narratives analysed reveal various socio-cognitive mechanisms. The informants report having initially experienced the autochthonous minority language as an obstacle but later on developed an alliance with it and with minority languages in general. This change seems to be influenced by positive affective socialisation experiences in the host society and by the growing perception that knowing the language makes them members of the community. Furthermore, the sociolinguistic situation is perceived as an alternative model for rethinking one's own language ideology. As a result, a mirror effect, or movements of reciprocity, emerges as the representation built in Catalonia is projected onto the homeland.